Silver nanoparticles loaded on lactose/alginate: in situ synthesis, catalytic degradation, and pH-dependent antibacterial activity - Tu, Nguyen Thi Thanh; Vo, T. Lan-Anh; Ho, T. Thu-Trang; Dang, Kim-Phuong T.; Le, Van-Dung; Minh, Phan Nhat; Dang, Chi-Hien; Tran, Vinh-Thien; Dang, Van-Su; Chi, Tran Thi Kim; Vu-Quang, Hieu; Fajgar, Radek; et al. (Beilstein Journal of Nanotechnology, 2023)
We present the in situ synthesis of silver nanoparticles (AgNPs) through ionotropic gelation utilizing the biodegradable saccharides lactose (Lac) and alginate (Alg). The lactose reduced silver ions to form AgNPs. The crystallite structure of the nanocomposite AgNPs@Lac/Alg, with a mean size of 4–6 nm, was confirmed by analytical techniques. The nanocomposite exhibited high catalytic performance in degrading the pollutants methyl orange and rhodamine B. The antibacterial activity of the nanocomposite is pH-dependent, related to the alterations in surface properties of the nanocomposite at different pH values. At pH 6, the nanocomposite demonstrated the highest antibacterial activity. These findings suggest that this nanocomposite has the potential to be tailored for specific applications in environmental and medicinal treatments, making it a highly promising material.
Keywords: alginate; bacterial activity; catalysis; lactose; silver nanoparticles; synthesis